Prophylactic salpingo-oophorectomy & surgical menopause for inherited risks of cancer: the need to identify biomarkers to assess the theoretical risk of premature coronary artery disease - Zarah Batulan; Nadia Maarouf; Vipul Shrivastava; Edward O'Brien (BMC, 2018)
Abstract Background Some women with genetic risk of breast and/or ovarian cancer (e.g., BRCA1/2) opt to undergo prophylactic salpingo-oophorectomy (PSO, or surgical removal of the ovaries & fallopian tubes) in order to reduce their risk of cancer. As a consequence, these women experience "surgical menopause" - accompanied by more severe climacteric symptoms that occur in a much shorter time frame. While the risk of coronary artery disease (CAD) rises with menopause, little is known about how the sudden loss of ovarian function from PSO alters the whole-body physiology, and whether it predisposes women to premature CAD. Methods/Design To manage CAD risk there is a prerequisite for reliable biomarkers that can help guide risk assessment and therapeutic interventions. To address these needs, this prospective, observational cohort study will evaluate surrogate markers reflective of CAD health in women experiencing surgical menopause after PSO. Twenty women representing each of the following groups will be enrolled over 3 years (total participants = 240): (i) pre-menopausal PSO, (ii) post-menopausal PSO, (iii) pre-menopausal women undergoing other pelvic surgery, and (iv) pre-menopausal controls (no surgery). All participants will provide blood plasma samples pre- and 1, 3, 6, & 12 months post-operatively, with serial samples collectively assessed for measurements of the study's primary endpoints of interest. These include a hormone profile (estradiol, follicle stimulating hormone (FSH), luteinizing hormone (LH), and progesterone) and both conventional (lipid profile) and novel biomarkers (Heat Shock Protein 27 (HSP27), HSP27-antibodies (HSP27 Ab), proprotein convertase subtilisin/kexin 9 (PCSK9), inflammatory cytokines) of CAD. Another aspect of this study is the measurement and analysis of retinal vessel diameters - an emerging physiological parameter reflective of CAD risk. Finally, a patient engagement exercise will result in the drafting of patient-generated questionnaires that address the well-being and health concerns of these women as they transition through premature menopause and work with our research team to identify and discuss their health priorities. Discussion The protocol of our planned study investigating the effects of PSO on CAD is described herein. Characterization of novel CAD markers in women experiencing surgical menopause will yield new insights into the role of the functional ovary in modulating lipid parameters and other CAD risk factors such as HSP27 and HSP27 Ab.